2012
DOI: 10.1021/ic3007525
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation Reactions Catalyzed by Vanadium Complexes of Bis(Phenolate) Ligands

Abstract: Vanadium(V) complexes of the tridentate bis(phenolate)pyridine ligand H(2)BPP (H(2)BPP = 2,6-(HOC(6)H(2)-2,4-(t)Bu(2))(2)NC(5)H(3)) and the bis(phenolate)amine ligand H(2)BPA (H(2)BPA = N,N-bis(2-hydroxy-4,5-dimethylbenzyl)propylamine) have been synthesized and characterized. The ability of the complexes to mediate the oxidative C-C bond cleavage of pinacol was tested. Reaction of the complex (BPP)V(V)(O)(O(i)Pr) (4) with pinacol afforded the monomeric vanadium(IV) product (BPP)V(IV)(O)(HO(i)Pr) (6) and aceton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 43 publications
3
58
0
Order By: Relevance
“…For example, Toste's group [1] developed a series of vanadium-oxo complexes and applied them to the non-oxidative cleavage of the C-O bonds of dimeric lignin model compounds to give aryl enones with 95% conversion. Hansen's group [2][3][4] also studied a vanadium complex catalyzed lignin model oxidation reaction, and reported that the C-O and C-C bonds could be selectively cleaved by changing the ligand involved in the catalysis [5]. The use of hydrogenation as another potential method for the conversion of lignin has also been the subject of considerable attention.…”
mentioning
confidence: 99%
“…For example, Toste's group [1] developed a series of vanadium-oxo complexes and applied them to the non-oxidative cleavage of the C-O bonds of dimeric lignin model compounds to give aryl enones with 95% conversion. Hansen's group [2][3][4] also studied a vanadium complex catalyzed lignin model oxidation reaction, and reported that the C-O and C-C bonds could be selectively cleaved by changing the ligand involved in the catalysis [5]. The use of hydrogenation as another potential method for the conversion of lignin has also been the subject of considerable attention.…”
mentioning
confidence: 99%
“…Studies on the stoichiometric oxidation of pinacol have been carried out also with complexes V2 and V3 [67]. Reaction of V2 with pinacol (5 equiv.)…”
Section: Methodsmentioning
confidence: 99%
“…In this case, the complete transformation of V3 into light purple reduced V16 was observed (Scheme 14), even if the reaction required longer E. Amadio et al / Coordination Chemistry Reviews xxx (2015) xxx-xxx Scheme 10. Vanadium complexes V1-11 used in aerobic oxidative carbon-carbon cleavage of diols [66,67,[86][87][88][89].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The 4-O-5 linkage (e.g., diaryl and aryl alkyl ethers) is a representative C-O linkage in lignin, and its catalytic cleavage is considered as an efficient way to depolymerize lignin for production of aromatics. [3,4,[6][7][8][9][10][11] Various metal catalysts such as Ni, [12][13][14][15] Ru, [16,17] Cu, [18][19][20][21] Pd/Zn, [22] V [23][24][25][26] and Fe, [27] have been reported for catalysing the cleavage of aryl C-O in lignin model compounds including diaryl ethers and aryl alkyl ethers via oxidation or hydrogenlysis. However, harsh reaction conditions including high temperature and complicated reaction systems are generally required, and the target product yields are relatively low.…”
Section: Introductionmentioning
confidence: 99%